PENGARUH KEPUASAN KERJA DUKUNGAN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMK SWASTA DI KECAMATAN SUMBERSARI - Madaam Anieq Fatati; Diana Sulianti K Tobing; Sri Wahyu Lelly Hana (STIE Mandala Jember, 2017)
This research includes explanatory research because it is intended to measure and analyze the presence or absence of influence of job satisfaction factors and organizational support for work motivation and teacher performance at SMK Private Sumbersari District Jember. Analyzer used in this research is path analysis. This is so that researchers can analyze the direct influence of each variable studied. The variables used are job satisfaction variable and organizational support as independent variable affecting work motivation variable as intervening and teacher performance as dependent variable. In this research the population is a teacher at SMK Swasta Sumbersari District Jember a number of 49 people consisting of 13 people as a teacher SMK Trunojoyo, 26 people as a teacher SMK Kartini and 10 people as teachers SMK Muh.Sroedji. The sampling technique used in this study is saturated or census sampling, where all members of the population are sampled.